Dimensões de Performance de Projetos Paisagísticos Contemporâneos na Orla Marítima de Salvador, Bahia - Serpa, Angelo (Paisagem e Ambiente, 2000)
Parque Costa Azul is one of the newest public spaces for sports, culture and leisure in Salvador. Inaugurated on 1997, it is a complex of 55,000 sq. meters, including a jogging track, a skating-rink, a biking track, playground with gym equipment, as well as restaurants, amphitheater and parking. Occupying the old Costa Azui C/ub, on the outskirts o f Salvador, the park is an alternative to entertainment, mainly for the inhabitants o f the neighboring areas, who, on weekends, would up choosing the beach as their main leisure option. From 1999, the city received a section of beach property that had been completely refurbished. The area between the Jardim dos Namorados and the Costa Azui, 100,000 sq. meters and 1.5 km long, received new equipment, and road traffic and lightning improvements. The two projects are characterized by the functionality of the subspaces and the absence of larger vegetation, with much construction on the grounds and artistic workmanships such as boards and sculptures. Colorful porches of differentiated forms, characteristic of contemporary landscaping, are present, demonstrating the influence of designs developed in Europe and United States. This work analyzes the trend towards homogenization of the designing language in the contemporary landscaping, as a consequence of globalization and internationalization of landscaping designs, on the basis of the concept of not-piace, proposed by authors such as Augê and Reiph. The "dimensions of performance" are examined - for both the projects - as proposed by Lynch in his "theory of good urban form"